Research on VVC Intra-Frame Bit Allocation Scheme Based on Significance Detection - Jin, Xuesong; Sun, Huiyuan; Zhang, Yuhang (Applied sciences, 2024)
This research is based on an intra-frame rate control algorithm based on the Versatile Video Coding (VVC) standard, considering that there is the phenomenon of over-allocating the bitrate of the end coding tree units (CTUs) in the bit allocation process, while the front CTUs are not effectively compressed. Fusing a Canny-based edge detection algorithm, a color contrast-based saliency detection algorithm, a Sum of Absolute Transformed Differences (SATD) based CTU coding complexity measure, and a Partial Least Squares (PLS) regression model, this paper proposes a CTU-level bit allocation improvement scheme for intra-mode code rate control of the VVC standard. First, natural images are selected to produce a lightweight dataset. Second, different metrics are utilized to obtain the significance and complexity values of each coding unit, the relatively important coding units in the whole frame are selected, which are adjusted with different weights, and the optimal adjustment multiplicity is supplemented into the dataset. Finally, the PLS regression model was used to obtain regression equations to refine the weights for adjusting the bit allocation. The proposed bit allocation scheme improves the average rate control accuracy by 0.453%, Y-PSNR by 0.05 dB, BD-rate savings by 0.33%, and BD-PSNR by 0.03 dB compared to the VVC standard rate control algorithm.